(untitled) (Our Nature, 2025)
A study was conducted to analyze the growth performance of mixed-sex Nile Tilapia (Oreochromis niloticus) with soyabean-enriched feed and moringa-enriched feed. The experiment was conducted for 75 days in a cemented tank (3 m x 2 m x 1 m) in a completely randomized design with three treatments in triplicate. The treatments include: T1 - Control (Homemade feed), T2 - homemade feed + 5% soybean meal, and T3 - homemade feed + 5% Moringa leaf powder. Nile tilapia fish were added to each tank at a rate of 5 fish/m2, with an average stocking weight of 7.7±0.3 g/fish. The fish were fed with designated feed at a rate of 3% of their body weight during the culture period. Different water quality parameters, such as water temperature, dissolved oxygen, and pH, were within the optimum range for fish culture. The average final weight was significantly higher (p<0.05) in T2 (27.60±0.10) and T3 (27.40±0.06) compared to T1 (26.01±0.10). Although there was no significant difference in survival rate among treatments (p > 0.05), the daily weight gain (DWG) was significantly greater (p < 0.05) in T2 (0.266 ± 0.004 g/day) and T3 (0.262 ± 0.02 g/day) compared to T1 (0.245 ± 0.003 g/day). The apparent feed conversion ratio (AFCR) was lowest in T3 (1.94 ± 0.02), indicating better feed utilization efficiency. In contrast, the feed conversion efficiency (FCE) was lowest in T1 (0.48 ± 0.012), meaning only 48% of the feed was converted into fish biomass. Thus, it can be concluded that the inclusion of plant-based ingredients such as soybean meal and moringa leaf powder in fish diets can significantly enhance growth performance and feed efficiency. Therefore, plant-based diets may serve as sustainable and effective alternatives to animal-based feeds in aquaculture.